Effect of corporate governance board leadership models and attributes on earnings quality of quoted nigerian companies - Cosmas Ikechukwu Asogwa; Grace Nyereugwu Ofoegbu; Judith Ima Nnam; Onyekachi David Chukwunwike (Cogent Business & Management, 2019)
Abstract: Purpose: This study examined the effect of corporate governance leadership models and attributes on firms' earnings quality using evidence from Nigerian quoted firms. Design/Methodology/Approach: This study used an ex-post facto design with a twostage multiple random and fixed effect regression analyses. A sample of 37 quoted firms in Nigerian Stock Exchange between 2014 and 2018 was selected for the study. Findings: Relative to unitary corporate leadership, dual board leadership model outperformed and significantly improves earnings persistence and value relevance. Earnings persistence and value relevance increased in boards where CEOs and board chairpersons have equal financial expertise. Also the quality of earnings improved significantly with a good mix of financial expertise and legal skills in the board. Thus, the capital market places a premium on such good leadership attribute mix. Research Limitation: This study concentrated on non-financial firms in Nigeria. Thus, it should not primarily be generalized as it is context-specific and most applicable among the developing economies Policy Implication: The implication is that investors can mitigate adverse portfolio selection if they target firms, where both CEOs and board chairpersons have strong accounting and legal knowledge mix. Investors should consider board leadership structures in assessing the overall firms' earnings quality. Leadership roles separation provides for higher reporting quality. Originality: This study provides the latest evidence of the effect of board leadership models and attributes on firms' earnings quality in Nigeria. It makes original contribution to the effect of corporate governance on earnings persistence and predictability and how the market reacts to certain attribute combinations.
Keywords: 650; corporate governance; board leadership models; chief executive officer; attributes; earrings quality